STRATEGIES AND TACTICS OF EFFECTIVE COMMUNCATION IN PROFESSIONAL SPHERE - E. A. Sidelnikova (Гуманитарные и юридические исследования)
Tolerance development is of great current interest in the modern world. It is important not only for indulgence enhancement of different social groups to each other, but also for signiicant increase of eficiency of the modern economy. The article highlights the issue of tolerant skills formation as student-journalists and linguists' competent component to achieve effective communication in professional sphere on the basis of economic texts. The main principle of studying is to develop skills and abilities to recognize lexico-grammatical structures, stylistic means, which are used in the text to gain harmonious communication or which lead to a communicative failure.